Stress and Coping in Caregivers of Children with RASopathies: Assessment of the Impact of Caregiver Conferences - Ganetsos, Athena; Farrelly, Ellyn; Magoulas, Pilar; Stevenson, David A. (Journal of Pediatric Genetics, 2020)
The study aimed to assess baseline stress and coping mechanisms among caregivers of children with RASopathies (i.e., cardiofaciocutaneous and Costello's syndrome) and the impact of attending biennial caregiver conferences. Caregivers completed the Perceived Stress Scale, Coping Health Inventory for Parents, and demographic surveys prior to family conferences, and 1- and 6-month postconferences. Baseline stress was increased and associated with child age, parental age, and number of conferences attended. After 1 month, caregiver stress was lowered among men and caregivers attending ≥2 support conferences.
Keywords: Costello syndrome; cardiofaciocutaneous syndrome; RASopathies